2016
DOI: 10.1111/ijn.12436
|View full text |Cite
|
Sign up to set email alerts
|

Building the capacity of nursing professionals in Cambodia: Insights from a bridging programme for faculty development

Abstract: To upgrade nursing instruction capacity in Cambodia, two bridging programmes were opened for the Bachelor of Science in Nursing simultaneously in-country and out-of-country (Thailand). A descriptive qualitative study was conducted to assess effectiveness of both programmes jointly and to explore needs concerning the further development of nursing education. This study included interviews with 34 current or previous programme participants (nursing instructors or hospital preceptors) and 10 managers of collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…In this study, the main areas of faculty training in previous research were upgrading knowledge and skills, teaching method, transforming theory into practice, research ability, leadership, and clinical education capacity as demonstrated in previous studies (3, 4, 6). Throughout this project, nursing curriculum redesign was focused on competency improvement of nursing graduates and problem-based learning as a new teaching method as demonstrated by Ghalenoei et al (17).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In this study, the main areas of faculty training in previous research were upgrading knowledge and skills, teaching method, transforming theory into practice, research ability, leadership, and clinical education capacity as demonstrated in previous studies (3, 4, 6). Throughout this project, nursing curriculum redesign was focused on competency improvement of nursing graduates and problem-based learning as a new teaching method as demonstrated by Ghalenoei et al (17).…”
Section: Discussionmentioning
confidence: 73%
“…However, there has been very little research on governance or administration training for nurses; it was good for capacity building through bottom-up and participatory approaches in project implementation. Koto et al (4) and Shin et al (16) highlighted the role of a self-governance body in a partner country as a way of bottom-up decision making. Though the formation of a nursing curriculum committee of this project was top-down rather than bottom-up, the members were very energetic and enthusiastic in making changes adopting problem-based teaching and learning methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Kirkpatrick's model, we assessed their 2) learning and 3) behavior and found the bene ts with both professional nursing practice and teaching after completing the upgrading courses. However, the immediate post-training study focused only on individual behavior outcomes, and we found these trainees were not well accepted by their nursing colleagues and other health professionals at their workplaces [10]. In this longterm, post-training study, we aimed to evaluate the 3) behavior and 4) results as long-term outcomes of these two training programs and identify in uencing factors by emphasizing institutional development of education and clinical facilities.…”
Section: Introductionmentioning
confidence: 99%